Groundwater availability for irrigation purposes: Case of Middle Cheliff aquifer Algeria - Nadjai, Saci; Khammar, Hichem; Bouchema, Nadhir; Nabed, Abdelkader Nadir; Bouderbala, Abdelkader; Benaabidate, Lahcen (Future Science, 2025)
The Middle Cheliff Plain faces persistent difficulties in manag-ing its limited groundwater reserves. This region, covering 321 km² in a semi-arid climate, is subjected to a detailed study of groundwater quality for irrigation purposes. In this context, twelve samples were carefully collected and analyzed. Nine es-sential parameters were evaluated, including physicochemical parameters and irrigation indices It is noted that the waters have an average conductivity of 4231 μs.cm-1 and a significant chloride content of 23.33 meq/l which has an unacceptable cat-egory for irrigation also the majority of the indices present fair-ly acceptable and permissible values for irrigation SAR and RSC (100%) of the samples respectively, also the PI 75% of the pie-zometers are suitable for irrigation These criteria were used to assess the suitability of groundwater for irrigation. In most of the plain, the Groundwater Quality Index for Irrigation (GWQII) indicates both acceptable and poor quality. These results show that most of these chemical constituents are above the FAO standards. Therefore, irrigation water poses a danger to the region's vast fields and its fragile crops. The proposed ap-proach has demonstrated efficacy in the assessment of groundwater quality for irrigation purposes, exhibiting versa-tility in application and adaptability across diverse geograph-ical regions, including humid, arid, and semi-arid settings worldwide.